The Effect of Service Quality on Tourist Satisfaction in The Implementation of CHSE at Museum Nasional Jakarta - Soemarni, Lyly; Huvianta, Harny (International Journal of Travel, Hospitality and Events, 2023)
Purpose: The study was to determine the effect of service quality on the implementation of CHSE on the level of tourist satisfaction while visiting Museum Nasional in Jakarta. Research Methods: The data used in this study are primary data obtained by distributing questionnaires to visitors of Museum Nasional aged 18 years and over and used purposive sampling. The analytical method used   is simple linear regression analysis. Results and discussion: The Museum Nasional has implemented CHSE in its operational activities quite well, this can be seen from the results of the survey data obtained in this study, although there are still parts of the service that must be improved. Implication: The quality of service in the CHSE implementation have a direct effect toward tourists’ satisfaction.   Keywords: CHSE, Tourist Satisfaction, Service Quality.